2020
DOI: 10.1108/hff-02-2020-0093
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of conjugate heat transfer and entropy generation of MHD natural convection of nanofluid in an inclined enclosure

Abstract: Purpose The purpose of this paper is to investigate conjugate heat transfer of natural convection and entropy generation of nanofluid in the presence of external magnetic field via numerical approach in an inclined square cavity enclosure. Design/methodology/approach Control volume finite volume method with collocated arrangement of grids was used for discretization of continuity, momentum, solid and fluid energy equations. Rhie and Chow interpolation technique was applied to avoid checkerboard problem in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The same authors have also explored the natural or double-diffusive phenomena in their research articles (Kumar et al , 2023b, 2021). Furthermore, several other researchers have also paid attention to studying the entropy generation in conventional physical domains (Shaker et al , 2022; Ishak et al , 2020; Tayebi and Chamkha, 2019; Kardgar, 2021; Hussain et al , 2018; Singh et al , 2015b; Alipanah et al , 2015; Das and Basak, 2017; Roşca et al , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The same authors have also explored the natural or double-diffusive phenomena in their research articles (Kumar et al , 2023b, 2021). Furthermore, several other researchers have also paid attention to studying the entropy generation in conventional physical domains (Shaker et al , 2022; Ishak et al , 2020; Tayebi and Chamkha, 2019; Kardgar, 2021; Hussain et al , 2018; Singh et al , 2015b; Alipanah et al , 2015; Das and Basak, 2017; Roşca et al , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Vijaybabu (2020) performed computational study to address the hot porous object impact on natural convective phenomena and irreversibilities in a cavity and found that the minimum EG depends on the permeability of cylinder. Kardgar (2021) examined the impact of Lorentz force on conduction–convection flow, thermal dissipation and EG of nanofluid filled in an inclined cavity. The collective effects of Lorentz force, chemical reaction and heat generation on the energy transport along with EG in a doubly stratified porous geometry have been studied by Kumar et al (2022a, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Conjugate heat transfer in a horizontal channel with wall-mounted obstacles is considered an attractive research topic due to the progress of high-performance electronic equipment in several engineering and industrial fields, particularly the cooling of the electronics system and the heat exchangers using different cooling systems depending on the studied fluid such as airor water-cooling system, and nanofluids cooling, which are mainly employed for their improved thermal properties as coolants in heat transfer devices such as heat exchangers, electronic cooling plates and radiators… 1,2 Therefore, many researchers adopt different numerical methods to investigate this type of problem. [3][4][5][6][7][8] Roy al. 9 analyzed experimentally the heat transfer of an array of aluminum obstacles in a horizontal airflow duct.…”
Section: Introductionmentioning
confidence: 99%